2022
DOI: 10.1002/jeq2.20342
|View full text |Cite
|
Sign up to set email alerts
|

Fall cover crop nitrogen uptake drives reductions in winter‐spring leaching

Abstract: Cover crops can reduce nitrate leaching after cash crop harvest. Despite widespread cover crop implementation, there has been a limited effect on water quality in the Chesapeake Bay watershed. We hypothesize that typical timing for Maryland cover crop planting after cash crop harvest is too late to allow roots to take up substantial nitrate from the soil profile before it is leached by winter drainage water. Across four site‐years (including sandy and silty soils), we compared various planting dates for a radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Early planted cover crops reduce fall NO 3 − leaching (Sedghi & Weil, 2022; Staver & Brinsfield, 1998; Thapa et al., 2018). Although delaying termination increases biomass and N uptake in the springtime, the timing of N uptake by cover crops is also important as NO 3 − leaching potential is highest in the fall–winter (Di & Cameron, 2002; Otte et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early planted cover crops reduce fall NO 3 − leaching (Sedghi & Weil, 2022; Staver & Brinsfield, 1998; Thapa et al., 2018). Although delaying termination increases biomass and N uptake in the springtime, the timing of N uptake by cover crops is also important as NO 3 − leaching potential is highest in the fall–winter (Di & Cameron, 2002; Otte et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of effective agronomic methods for cover crop management can be encouraged by varying incentives in the MACS Winter Cover Crop Program, and payment rates change from year to year based upon program objectives, expert knowledge, and availability of funding (Bradley, 2022; Maryland Department of Agriculture, 2019). Early planted cover crops (planted at least 2 wk prior to the first frost) take up N more effectively and reduce fall NO 3 − leaching (Sedghi & Weil, 2022; Staver & Brinsfield, 1998; Thapa et al., 2018). Whereas delaying termination in the springtime increases biomass production and N uptake, the timing of N uptake by cover crops is important as NO 3 − leaching potential is highest in the fall–winter (Di & Cameron, 2002; Otte et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Soil inorganic nitrogen pools mediate the relationship between fall sowing date (fall GDDs) and total cereal rye biomass production (Mirsky et al 2017). Sedghi and Weil (2022) report that fall sowing dates that are typical for Maryland when following lateharvested grain crops (i.e., October) will likely result in greater nitrogen leaching because of insufficient cereal rye growth necessary to immobilize NO 3 -N through the soil profile. The marginal cereal rye biomass response to spring nitrogen applications in our Delaware experiments may be attributed to the combination of lack of soil nitrogen at planting due to leaching potential in coarse soils and insufficient fall GDDs needed for cereal rye growth to optimize nitrogen uptake in early spring.…”
Section: Management Implicationsmentioning
confidence: 99%
“…If not captured by deep-rooted cover crops, this deep soil NO 3 will likely leach to groundwater over winter. Cover crops most effectively reduce NO 3 leached when given enough growing time to produce large biomass and deep roots (Kristensen and Thorup-Kristensen 2004;Thorup-Kristensen et al 2009;Yang et al 2014;Wahlström et al 2015;Christopher et al 2021;Sedghi and Weil 2022). Early planting of cover crops may therefore drive reductions in NO 3 leaching.…”
mentioning
confidence: 99%
“…A meta-analysis by Thapa et al (2018b) reported that cereal rye (Secale cereal)-hairy vetch (Vicia villosa Roth) cover crop mixtures can accumulate more spring biomass than either species planted separately, and the hairy vetch can fix as much or more N in the mixture in spring than when grown alone. When radish is planted with a winter-hardy cereal, N released by frost-kill may be taken up by the cereal, thus reducing NO 3 leached relative to a pure radish stand (Gaimaro et al 2022;Sedghi and Weil 2022). Hirsh et al (2021) reported that an early-planted forage radish-cereal cover crop may be more effective at cycling N than either species separately.…”
mentioning
confidence: 99%